Assessment of high-frequency technologies for determining the moisture content of comminuted solid wood fuels. Issue 1 (1st January 2016) - Fernandez-Lacruz, Raul; Bergström, Dan
Abstract: Industries that trade in biomaterials require new and reliable methods for rapidly determining the moisture content (MC) of solid biomass. It is therefore important to develop and test alternative technologies that can fulfil the requirements of all parties in the wood fuel trading chain and provide real-time, accurate and representative MC measurements. The aim of this study was to evaluate the accuracy of a commercial high-frequency (HF) technology (originally developed to analyse potting soils) as a tool for determining the MC of comminuted solid biofuels. The measurements obtained using the HF technology were compared to measurements obtained using the gravimetric method from the European standard EN 14774-2:2009. The HF measurements were most accurate for feedstocks with homogeneous particle size distributions such as wood chips, sawdust and peat [root mean square error (RMSE) 3.1–4.5%]. Less accurate results were achieved for wood fuels with large particles and gaps between particles, such as crushed stem wood (RMSE 8.4%). If the system was adapted to improve its performance for heterogeneous particle size distributions, it should yield acceptably accurate MC estimates. Because of its potential in online analysis, it should therefore be regarded as a potential alternative to existing methods for MC measurement and merits further investigation.